Lifetime Prevalence of Attention-Deficit Hyperactivity Disorder in Young Adults: Examining Variations in the Socioeconomic Gradient. (October 2015) - Yallop, Lauren; Brownell, Marni; Chateau, Dan; Walker, John; Warren, Michelle; Bailis, Dan; LeBow, Michael
Objective: It has only recently been accepted that attention-deficit hyperactivity disorder (ADHD) persists into adulthood. Accordingly, less is known about adult diagnostic and treatment prevalence. We aimed to determine the lifetime prevalence of ADHD diagnosis and psychostimulant prescriptions for young adults in the province of Manitoba and to explore how diagnosis differs according to sociodemographic characteristics and age at diagnosis; and to investigate whether a socioeconomic gradient exists within young adults with a lifetime ADHD diagnosis, as well as the variables that moderate the gradient. Methods: Using the Manitoba Population Health Research Data Repository, our cross-sectional analysis used 24 fiscal years of data (1984/85 to 2008/09) and included all adults aged 18 to 29 during 2007/08 to 2008/09 in Manitoba ( n = 207 544) who had a lifetime diagnosis of ADHD ( n = 14 762). Regression analyses tested for differences in rates by sex, region, age, age at diagnosis, and socioeconomic status. Results: Lifetime prevalence for ADHD diagnosis (7.11%) and psychostimulant prescriptions (3.09%) differed according to sex, region, and age. In contrast to previous Manitoban research on childhood ADHD, the socioeconomic gradient for ADHD diagnosis was not found in young adulthood. When region was accounted for, a small negative gradient in the urban population and a positive gradient in the rural population were evident. People from the highest income quintile were significantly less likely to be diagnosed before age 18, compared with other income quintiles. Conclusions: Given the high lifetime prevalence of ADHD in Manitoban young adults and significant socioeconomic correlates for diagnosis, further investigation into the trajectory of this relatively unexplored population is recommended.